Analisis Peran Digital Marketing dan Inovasi Produk dalam Meningkatkan Daya Saing UMKM Fashion di Indonesia: Kajian Literatur - Shintya Carolina; Yorina An’guna Bansa (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
The competitiveness of fashion MSMEs in Indonesia faces major challenges due to rapid market changes, digital technology development, and increasingly intense competition at both local and global levels. In this context, digital marketing and product innovation have become key strategies to strengthen market position and ensure business sustainability in the dynamic fashion industry. This study aims to analyze in depth the role of digital marketing and product innovation in enhancing the competitiveness of fashion MSMEs in Indonesia. Using a systematic literature review (SLR) approach, relevant scholarly articles published between 2015 and 2025 were collected and critically analyzed from databases such as Scopus, ScienceDirect, and Google Scholar. The findings indicate that the effective implementation of digital marketing contributes to improved brand awareness, customer engagement, and sales performance. Meanwhile, product innovation plays an essential role in supporting product differentiation, strengthening customer loyalty, and creating added value that enhances brand attractiveness. Tongue Fashion MSMEs that successfully integrate digital marketing strategies with continuous product innovation tend to demonstrate stronger resilience to market changes and better adaptability to evolving consumer preferences. Therefore, strengthening digital capabilities, enhancing design creativity, and fostering collaboration with various stakeholders are strategic steps for achieving sustainable growth. This study provides theoretical implications through the development of a conceptual framework that links digital marketing, product innovation, and MSME competitiveness. In addition, it offers practical recommendations for MSME practitioners to adopt integrated, technology-based, and innovation-driven strategies to compete effectively in the modern fashion industry.